SARKASME DALAM KOMUNIKASI ANGGOTA GRUP 2STROKE BELIDA DARAT PERSPEKTIF HERMENEUTIKA PAUL RICOEUR - Piljanah, Lailati (Fakultas Dakwah Institut Dirosat Islamiyah Al-Amien Prenduan, 2024)
ABSTRACTSarcasm (rude word) is a rude or harsh language style that contains negative meanings and is used for ridicule and innuendo. In addition, sarkarme can be a positive meaning depending on the context of the conversation. As for this study, the researchers used Paul Ricoeur hermeneutics analysis (interpreter, text/word, historical context and cultural context) with qualitative methods and data collection techniques through interviews, observation and documentation. This study aims to determine the form of sarcasm (rude words) in the communication of members of the motor Group 2stroke Belida Darat, and determine the context and social relationships of sarcasm (rude words) in the communication of members of the group 2stroke Belida Darat. So based on the results of the study, the findings of the study are 1) forms of sarcasm expressed by members of the grub motor 2stroke Belida Darat is sarcasm in the form of animal names: dogs, cats and pigs. Objects with bad characteristics in the form of: Bengkai and Tai. Human condition or state in the form of: Gile and Lolo. Family members are: Kampang. And cool languages in the form of: Anjay and Anying. 2) in the context of humorous and emotion and influenced by mass culture and social relations in the form of social media.Keyword: Sarcasm, Motor Grub, Hermeneutics Paul Ricoeur